SUFISM AND MORAL LEADERSHIP IN ISLAMIC POLITICAL DEVELOPMENT: The Ethical Infrastructure of Sheikh Musthafa Husein Nasution in North Sumatra - Saipul Bahri; Mohd Syakir Bin Mohd Rosdi; Heri Kusmanto (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2026)
This article examines the sufistic thought of Sheikh Musthafa Husein Nasution and its significance for Islamic political development in North Sumatra. Existing studies on sufism often treat it as a personal spiritual tradition, leaving its role in shaping political ethics and leadership practices underexplored, particularly at the regional level. Employing a qualitative approach based on library research, historical analysis, and in-depth interviews with political and community leaders, this study analyzes how Nasution integrated sufistic values into leadership formation, governance practices, and political regeneration. The findings reveal that sufism in Nasution’s thought functions as an ethical infrastructure that underpins Islamic political development through moral leadership formation, disciplined political conduct, service-oriented leadership, and long-term cadreization. By grounding political authority in tazkiyah al-nafs, spiritual accountability, and public welfare (mashlahah), Nasution’s model challenges technocratic and transactional approaches to development. This study contributes to Islamic political studies by repositioning Sufism as a normative and analytical framework for value-based political development in plural Muslim societies.